Virology. - ClinicalKey eBooks (Orlando, Fla. : Academic Press, 1955)
Contains abstracts only, 1993-1994; articles, 1995-
Description based on: Vol. 213, no. 2 (Nov. 10, 1995); title from title information screen.
Latest issue consulted: Vol. 450/451 (Feb. 2014) (ScienceDirect website, viewed Feb. 24, 2014).
Elsevier
Keywords: Virology -- Periodicals; Virologie -- Périodiques.; Virology; Virology; Electronic books